Keefektifan Layanan Konseling Kelompok Teknik Cognitive Restructuring dalam Mengatasi Nomophobia pada Siswa - Salma Nazella Fortuna; Ulfa Danni Rosada (Guidance : Jurnal Bimbingan dan Konseling, 2022)
In general, humans are social creatures who are never free from problems, one of which is anxiety when away from a smartphone or what is called nomophobia. This happens among the millennial generation, especially among teenagers. The aim of this study was to determine the effectiveness of group counseling services using cognitive restructuring techniques for students at SMA Negeri 8 Tasikmalaya City. This analytical method uses a pre-experimental one group pretest posttest based on paired t test samples. The results of the analysis show Asymp.sig. (2 tailed) is 0.000 less than <0.05, so it can be concluded "Hypothesis accepted" means that there is a difference between restructuring technique group counseling services for pretest and posttest, so it can be concluded "Counseling services with cognitive restructuring effective for overcoming nomophobia ” by using a focused approach to diverting the mind, namely developing hobbies such as reading, playing music and exercising